Effects of "Eight-Point Regulation" and "Chinese Military Bans Luxury Banquets" on Price, Sale, and Consumption of High-End Alcohol Products in China - Xianglong Xu; Runzhi Zhu; Sha Deng; Sheng Liu; Dengyuan Liu; Cesar Reis; Manoj Sharma; Yong Zhao (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
Background: Alcohol use disorder was linked to corruption, abuse of power, and bureaucratic ineffi  ciency in mainland China. The Communist Party of China issued the "Eight-Point Regulation" and "Luxury Banquets Ban for Chinese Military" in December 2012 to eliminate extravagance and corruption. This study aimed to probe the effects of "Eight-point regulation" and "Chinese military bans luxury banquets" on price, sale, and consumption of high-end alcohol products in China. Methods: We collected and analyzed secondary data to derive refl ections on the infl uence of the policies on alcohol sale and consumption, and discussed the remaining challenges in this area. In addition, we made suggestions for additional research and policy development. The data was obtained from offi cial websites, published studies, and research institutes. Qualitative and quantitative data were processed using MAXQDA 11. Results: The "Eight-Point Regulation" and the "Chinese Military Bans Luxury Banquets" have caused adjustments in sales mode, mode innovation, structural adjustment, and substitutes in the liquor industry. This study investigated the effect of the frugality rules on alcohol price, sales, and consumption: lowest growth on prices, decline in high-end liquor sales, and increase in sales ranking of middle- and low-end liquors. Conclusion: The identifi cation of this link is meaningful and may establish a model to improve public health in a top-down setting. The effective and continuous implementation of the rules may help reduce alcohol-related diseases as well as prevent chronic related conditions in the population. What's more, it was nearly four years since the two policies has been introduced. Further research should be conducted to investigate